An empirical, in-depth investigation into service creation in H.323 Version 4 Networks - Penton, Jason Barry (Rhodes University, Faculty of Science, Department of Computer Science, 2003)
Over the past few years there has been an increasing tendency to carry voice on IP networks as opposed to the PSTN and other switched circuit networks. Initially this trend was favoured due to reduced costs but occurred at the expense of sacrificing the quality of the voice communications. Switched circuit networks have therefore remained the preferred carrier-grade voice communication network, but this is again changing. The advancement in improved quality of service (QoS) of real-time traffic on the IP network is a contributing factor to the anticipated future of the IP network supplying carrier-grade voice communications. Another contributing factor is the possibility of creating a new range of innovative, state-of-the-art telephony and communications services that acquire leverage through the intelligence and flexibility of the IP network. The latter has yet to be fully explored. Various protocols exist that facilitate the transport of voice and other media on IP networks. The most well known and widely supported of these is H.323. This work presents and discusses H.323 version 4 service creation. The work also categorises the various H.323 services and presents the mechanisms provided by H.323 version 4 that have facilitated the development of the three services I have developed, EmailReader, Telgo323 and CANS.
Keywords: Computer programming; Computer networks; Computer network protocols